Covariations between personality behaviors and metabolic/performance traits in an Asian agamid lizard (Phrynocephalus vlangalii) - Chen, Jingfeng (PeerJ, 2019)
Ecological factors related to predation risks and foraging play major roles in determining which behavioral traits may mediate life history trade-offs and, therefore, the pace-of-life syndrome (POLS) structure among behavioral, physiological, and life-history traits. It has been proposed that activity/exploration or risk-taking behaviors are more likely to impact resource acquisition for organisms (individuals, populations, and species) foraging on clumped and ephemeral food sources than for organisms foraging on abundant and evenly distributed resources. In contrast, vigilance or freezing behavior would be expected to covary with the pace of life when organisms rely on food items requiring long bouts of handling. Nevertheless, it remains unclear how general this pattern is. We tested this hypothesis by examining the associations between exploration/risk-taking behaviors and metabolic/performance traits for the viviparous agamid lizard, Phrynocephalus vlangalii. This species forages on sparse and patchy food sources. The results showed positive correlations between exploration and endurance capacity, and between bite force and risk-taking willingness. Our current findings, in conjunction with our previous work showed no correlations between freezing behavior and performance in this species, support the idea that behaviors in life-history trade-offs are natural history-dependent in P. vlangalii, and provide evidence that behavioral types play functional roles in life history trade-offs to supporting POLS hypothesis.